Frankly Feminist : Short Stories by Jewish Women from Lilith Magazine - McDonough, Yona Zeldis; Schneider, Susan Weidman (Book collections on Project MUSE., 2022)
"A groundbreaking Jewish feminist short story collection. Short story collections focusing on Jewish writers have typically given women authors short shrift. This new volume represents the best Jewish feminist fiction published in Lilith Magazine and does what no other collection has done before in its geographic scope. It showcases a wide range of stories offering variegated cultures and contexts and points of view: Persian Jews; a Biblical matriarch; an Ethiopian mother in modern Israel; suburban American teens; Eastern European academics; a sexual questioner; a Jew by choice; a new immigrant escaping her Lower East Side sweatshop; a Black Jewish marcher for justice; in Vichy France, a toddler's mother hiding out; and more. Organized by theme, the stories in this book emphasize a breadth of content. Readers will appreciate the liveliness of burgeoning self-awareness captured in each tale, and the occasional funny, call-your-friend-and-tell-her-about-it moment. Skip around, encounter an author whose other writing you may know, be enticed by a title, or an opening line. You will find both pleasure and enlightenment-and even perhaps revelation-within these pages"--